Index Pembangunan Manusia, Inflasi, dan Pertumbuhan Ekonomi: Apa yang Data Tunjukkan untuk Indonesia pada Tahun 1990-2017? - Febrika Yogie Hermanto; Mar’atus Sholikah (Nomicpedia: Journal of Economics and Business Innovation, 2021)
This study aims to analyze the effect of the Human Development Index and Inflation on Indonesia's Economic Growth partially or simultaneously in 1990-2017. The data collection technique is done by using the purposive sampling technique, and by using the method of documentation. This study uses multiple linear regression analysis using time series data. This study shows that the Human Development Index has no significant effect on Economic Growth, while inflation has a very significant effect on Indonesia's Economic Growth, partially. Furthermore, the Human Development Index and Inflation have a significant effect on Indonesia's Economic Growth, simultaneously.